Antiviral Ability of Kalanchoe gracilis Leaf Extract against Enterovirus 71 and Coxsackievirus A16. (15th May 2012) - Wang, Ching-Ying; Huang, Shun-Chueh; Zhang, Yongjun; Lai, Zhen-Rung; Kung, Szu-Hao; Chang, Yuan-Shiun; Lin, Cheng-Wen
Abstract : Pandemic infection or reemergence of Enterovirus 71 (EV71) and coxsackievirus A16 (CVA16) occurs in tropical and subtropical regions, being associated with hand-foot-and-mouth disease, herpangina, aseptic meningitis, brain stem encephalitis, pulmonary edema, and paralysis. However, effective therapeutic drugs against EV71 and CVA16 are rare. Kalanchoe gracilis (L.) DC is used for the treatment of injuries, pain, and inflammation. This study investigated antiviral effects of K. gracilis leaf extract on EV71 and CVA16 replications. HPLC analysis with a C-18 reverse phase column showed fingerprint profiles of K. gracilis leaf extract had 15 chromatographic peaks. UV/vis absorption spectra revealed peaks 5, 12, and 15 as ferulic acid, quercetin, and kaempferol, respectively. K. gracilis leaf extract showed little cytotoxicity, but exhibited concentration-dependent antiviral activities including cytopathic effect, plaque, and virus yield reductions. K. gracilis leaf extract was shown to be more potent in antiviral activity than ferulic acid, quercetin, and kaempferol, significantly inhibiting in vitro replication of EV71 (IC 50 = 35.88 μg/mL) and CVA16 (IC 50 = 42.91 μg/mL). Moreover, K. gracilis leaf extract is a safe antienteroviral agent with the inactivation of viral 2A protease and reduction of IL-6 and RANTES expressions.